2020
DOI: 10.7759/cureus.8475
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis Dissecans Superficialis: Malign Appearance of a Benign Pathology

Abstract: Esophagitis dissecans superficialis (EDS), also known as sloughing esophagitis, is a very rare condition and may affect the whole esophagus, resulting in complete sloughing of the mucous membrane. EDS has been associated with various medications and dermatological conditions. In our case, EDS was suspected secondary to methotrexate treatment in a patient with Crohn's disease, although the definitive etiology remains unknown. It is very important for physicians to recognize the endoscopic appearance of EDS to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
0
6
0
1
Order By: Relevance
“…A retrospective study of 21497 EGD cases reported an EDS incidence of 0.03% [ 8 ]. The low incidence in combination with the typical contamination of biopsies with bacteria and fungi has led to frequent misdiagnosis and underreporting of EDS [ 1 , 3 , 9 ]. To date, there is no standardized therapy for EDS, as many of the cases are self-limiting with no long-term complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of 21497 EGD cases reported an EDS incidence of 0.03% [ 8 ]. The low incidence in combination with the typical contamination of biopsies with bacteria and fungi has led to frequent misdiagnosis and underreporting of EDS [ 1 , 3 , 9 ]. To date, there is no standardized therapy for EDS, as many of the cases are self-limiting with no long-term complications.…”
Section: Discussionmentioning
confidence: 99%
“…There is speculation that autoimmune-related EDS responds well to steroids, and Jaben et al described an idiopathic case of EDS that responded well to steroids [ 5 ]. A follow-up endoscopy at eight weeks has been proposed by some authors but enough evidence does not yet support its benefit [ 9 ]. With the initiation of high-dose pantoprazole and stopping oral diclofenac, our patient had complete resolution of symptoms and was discharged home in good health.…”
Section: Discussionmentioning
confidence: 99%
“…7 Occasionally, the patient may present with obstructive symptoms due to esophageal casts. 9 EDS is often confused with candida esophagitis, so it mandates pathological evaluation by taking a biopsy specimen, though candida may be seen in some cases without active inflammation. 7,10 Management of EDS varies based on the patients' severity of symptoms and underlying risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EDS are usually asymptomatic but can present with dyspepsia, dysphagia, odynophagia, heartburn, regurgitation, weight loss, and upper gastrointestinal bleeding [8]. In the REFLECT trial, the most common adverse events of lenvatinib therapy included hypertension, decreased appetite, weight loss, and diarrhea [9].…”
Section: Discussionmentioning
confidence: 99%